2021
DOI: 10.33084/bjop.v4i4.2890
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Antioxidant Activity of Melothria scabra Naudin Fruits

Abstract: The fruit of Melothria scabra Naudin is traditionally used by natives of South East Sulawesi and has economic values in the local markets. Nonetheless, little scientific information was gained from this plant to support its development for nutraceutical and pharmaceutical aspects. This study aimed to investigate the phytochemicals contained in the ethanol extract and organic fractions (methanol, ethyl acetate, and hexane) of the fruits using specific reagents and an LC-MS/MS analysis, as well as to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The plant extract exhibited antioxidant and anti-cancer activity (60-90%) against G361 and A549 cell lines [49]. By using LC-MS/MS, the same substance was also found in the ethanol extract of M. scabra fruits, and strong radical scavenger activities were reported with values varying from 20.7 to 37.5 g/mL [50]. Likewise, Chaiwong et al [51] reported this compound in the aqueous extract of dried mulberry fruit using (±) ESI-QTOF-MS/MS.…”
Section: Phytochemical Composition Of Ppme By Liquid Chromatography -...mentioning
confidence: 72%
“…The plant extract exhibited antioxidant and anti-cancer activity (60-90%) against G361 and A549 cell lines [49]. By using LC-MS/MS, the same substance was also found in the ethanol extract of M. scabra fruits, and strong radical scavenger activities were reported with values varying from 20.7 to 37.5 g/mL [50]. Likewise, Chaiwong et al [51] reported this compound in the aqueous extract of dried mulberry fruit using (±) ESI-QTOF-MS/MS.…”
Section: Phytochemical Composition Of Ppme By Liquid Chromatography -...mentioning
confidence: 72%
“…Historical studies by Fowden have shown biochemical composition within M. scabra, which could be useful for other comparisons in the future (Fowden 1965). Current research by Kamaruddin et al shows the anti-oxidant activity of M. scabra, as well as the chemical composition of extracts from this plant (Kamaruddin et al, 2021). Preliminary research conducted by Govindula et al suggests anti-diabetic and hypoglycemic properties of M. scabra (Govindula et al, 2019).…”
Section: Medical and Pharmacological Usementioning
confidence: 99%
“…Cucamelon, also known as Mexican miniature watermelon (Melothria scabra Naudin), is a horticultural crop from the Cucurbitaceae family [1]. It is a diploid (2n = 2× = 24) plant species that originated from Mexico and Central America but has spread widely across other regions of the world [2].…”
Section: Introductionmentioning
confidence: 99%
“…Cucamelon is cultivated for its diminutive, edible fruit, which resembles a miniature striped watermelon (Citrullus lanatus). Morphologically, the fruit is oval with an average length of 2.4 cm and a width of 1.5 cm and is consumed either in its raw form or processed as pickles and vegetables [1,3]. The fruits of M. scabra contain alkaloids, tannins, flavonoids, terpenoids, and saponins [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation